2009
DOI: 10.1002/ejoc.200900802
|View full text |Cite
|
Sign up to set email alerts
|

Base‐ and Copper‐Catalysed Condensation of Primary Activated Nitro Compounds with Enolisable Compounds

Abstract: Primary nitro compounds have not been employed as nitrile oxide precursors in reactions with active methylene compounds because the reagents commonly used as dehydrating agents also react with these dipolarophiles. However, the CuII‐catalysed cycloaddition/condensation procedure has been shown to be viable with these substrates, leading directly to the expected polyfunctional isoxazoles provided nitro compounds with enhanced acidity (“activated”) were used. In the absence of added dipolarophiles, these nitro c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…1–4 The synthesis of aryl-isoxazoles is also the subject of on-going improvements. 1,57 In connection with our studies on aryl isoxazole amides (AIMs) 89 we have reported lead compounds, which possess (1) useful antitumor activity and (2) photophysical properties, which are of potential diagnostic use as ‘tumor paint’. 10 …”
Section: Introductionmentioning
confidence: 99%
“…1–4 The synthesis of aryl-isoxazoles is also the subject of on-going improvements. 1,57 In connection with our studies on aryl isoxazole amides (AIMs) 89 we have reported lead compounds, which possess (1) useful antitumor activity and (2) photophysical properties, which are of potential diagnostic use as ‘tumor paint’. 10 …”
Section: Introductionmentioning
confidence: 99%
“…[7][8] In general, the key intermediate nitrile oxide is generated in situ by oxidative dehydrogenation of an oxime [7] or dehydrochlorination of a hydroximoyl chloride. [8] As an alternative strategy, Machetti and co-workers reported the condensation of nitro compounds with dipolarophiles, such as alkynes, [9] alkenes, [10] and diketones, [11] promoted by a strong base. However, a long period of heating (over days) was critical for the generation of the nitrile oxide by dehydroxylation of the nitro compound.…”
mentioning
confidence: 99%
“…9 Recently, Trogu et al synthesized a similar framework by the copper catalyzed cycloaddition/condensation of β-diketones with several functionalized nitrile oxides derived from α-nitrated carbonyl compounds. 10 In contrast to these successful studies using β-diketones, less reactive β-keto esters 20 have not been employed as dipolarophiles for nitrile oxide cycloadditions except for a few examples that suffer from limited scope 11 and low yields. 10,12 These facts and our experimental results strongly encouraged us to study the cycloaddition of carbamoyl nitrile oxide 2 with β-keto esters as well as β- In order to realize the abovementioned reactivities, the HOMO/LUMO energy gaps between nitrile oxides 2, 9, 10 and enolates 4a,b or enols 11a,b were estimated by DFT methods using B3LYP 6-31G+(d,p) in advance (Table 1).…”
mentioning
confidence: 99%
“…10 In contrast to these successful studies using β-diketones, less reactive β-keto esters 20 have not been employed as dipolarophiles for nitrile oxide cycloadditions except for a few examples that suffer from limited scope 11 and low yields. 10,12 These facts and our experimental results strongly encouraged us to study the cycloaddition of carbamoyl nitrile oxide 2 with β-keto esters as well as β- In order to realize the abovementioned reactivities, the HOMO/LUMO energy gaps between nitrile oxides 2, 9, 10 and enolates 4a,b or enols 11a,b were estimated by DFT methods using B3LYP 6-31G+(d,p) in advance (Table 1). In the 30 cycloadditions of phenylnitrile oxide 10 (Ar = Ph) with 1,3-dicarbonyl compounds 11a,b, the conversion of dipolarophiles to the corresponding enolates 4a,b seems to be somewhat advantageous.…”
mentioning
confidence: 99%
See 1 more Smart Citation